Different Patient Subgroup Different Maintenance, Proteasome Inhibitors or Immunomodulators Maintenance for Newly Diagnosed Multiple Myeloma: A 7-Year Single-Center Data in China - Han, Xiaoyan; Jin, Chunxiang; Zheng, Gaofeng; He, Donghua; Zhao, Yi; Li, Yi; Wu, Wenjun; Zheng, Weiyan; Wei, Guoqing; Zhang, Enfan; Huang, He; He, Jingsong; et al. (Frontiers in Oncology, 2021)
Introduction We analyzed different patient subgroups to determine optimal maintenance therapy in newly diagnosed multiple myeloma (NDMM) patients. Methods A total of 226 NDMM patients in our center were included in the study. The characteristics, survival, and adverse reactions were compared among patients who received maintenance therapy or not, and patients who received proteasome inhibitors (PIs) or immunomodulators (IMiDs) maintenance. The survival of different maintenance durations of bortezomib-based regimens was also analyzed. Results The maintenance therapy not only upgraded more patient responses (34.3 vs 13.3%, P = 0.006), but also significantly prolonged their progression-free survival (PFS) (median PFS: 41.1 vs 10.5 months, P < 0.001) and overall survival (OS) (median OS: not reached vs 38.6 months, P < 0.001). Compared with IMiDs, the PFS (median PFS: 43.7 vs 38.5 months, P = 0.034) and OS (median OS: not reached vs 78.5 months, P = 0.041) were both enhanced by PIs maintenance. Patients younger than 65 years who received PIs had a significantly prolonged OS (P = 0.032). Patients achieving only a partial response (PR) after induction and consolidation therapy had significantly longer PFS and OS after PIs maintenance compared to IMiDs (P = 0.007, 0.002). High-risk patients (ISS 2–3, DS 2–3, and RISS 2–3) given PIs maintenance benefit from a prolonged PFS (P = 0.002, 0.02, 0.06) and OS (P = 0.059, 0.047, 0.044, respectively) compared with IMiDs therapy. OS was significantly prolonged in patients who received ≥ 12 months of bortezomib-based maintenance therapy compared to those who were treated for < 12 months (P < 0.001), but no difference was observed in OS between patients who received 12 to 24 or ≥ 24 months of bortezomib-based maintenance therapy (P = 0.292). Conclusion PIs maintenance was superior to IMiDs in overall PFS and OS. The beneficial effect was most evident in patients achieving PR after induction and consolidation therapy, and in high-risk patients. Moreover, younger patients also benefited from PIs maintenance with an increased OS. A bortezomib-based maintenance therapy duration of 12 to 24 months after induction and consolidation therapy produced satisfactory OS.